The core-assisted mesh protocol. - Garcia-Luna-Aceves, J.J (IEEE Journal on selected areas in communications)
The core-assisted mesh protocol (CAMP) is introduced for multicast routing in ad hoc networks. CAMP generalizes the notion of core-based trees introduced for internet multicasting into multicast meshes that have much richer connectivity than trees. A shared multicast mesh is defined for each multicast group; the main goal of using such meshes is to maintain the connectivity of multicast groups even while network routers move frequently, CAMP consists of the maintenance of multicast meshes and loop-free packet forwarding over such meshes. Within the multicast mesh of a group, packets from any source in the group are forwarded along the reverse shortest path to the source, just as in traditional multicast protocols based on source-based trees. CAMP guarantees that within a finite time, every receiver of a multicast group has a reverse shortest path to each source of the multicast group. Multicast packets for a group are forwarded along the shortest paths front sources to receivers defined within the group's mesh. CAMP uses cores only to limit the traffic needed for a router to join a multicast group; the failure of cores does not stop packet forwarding or the process of maintaining the multicast meshes